Nutrient adequacy of diets of women of childbearing age in south-east Nigeria - Onyeji, Gertrude Nneka; Sanusi , Rasaki Ajani (Progress in Nutrition, 2022)
Abstract. Background and objective: Inadequate nutrients intake by women of child bearing age leads to reproductive health problems, resulting in maternal and infant mortality. The study aimed to evaluate nutrient adequacy of women of child-bearing age in South-east Nigeria. Methods and study design: In this cross sectional study, stratified random sampling and simple random sampling techniques were used to select 1200 women of child bearing age (15-49 years) from three states of South-east Nigeria. A 24-hour dietary recall questionnaire data were analysed using adapted Total Dietary Assessment (TDA) Software. Minimum Dietary diversity of Women of Reproductive Age (MDD-WRA) was calculated based on ten food groups with a cut-off point of intake at ≥5 groups. Nutrient Adequacy Ratio (NAR) was derived for energy and 11 other nutrients. Results: Mean age of the women was 28.2±5.6 years. BMI was 26.8±4.8 /m2. Majority (96.3%) women were married, 41.7% were traders. Mean dietary diversity score (MDDS) was 5.78 ±1.16 and 88.3% % of WRA achieved MDD-W. About 88.4% had high dietary diversity tercile (DDT) and 11.7% had low (DDT). Imo State with MDDS of (5.99±1.14) was significantly higher (P<0.05) than Enugu State (5.69±1.14) and Anambra State (5.64 ± 1.18). More than 50% did not meet their NAR values for Fat, calcium, vitamin C, Sodium, Potassium and Magnesium. Conclusions: Nutrient adequacy ratio indicated low in intake of some micro nutrients and excess intake of energy, carbohydrate and protein. Nutrition education is recommended in South-east Nigeria. Keywords: Women of reproductive age, Dietary Diversity, Nutrient Adequacy, Food groups, BMI